Spatiotemporal crosstalk among mitochondrial dynamics, NLRP3 inflammasome activation, and histone lactylation drives α-synuclein pathology in prodromal Parkinson’s disease - Lv, Peizhu; Chen, Xia; Liu, Shiping; Zhang, Yu; Bai, Yan; Wang, Shun; Wang, Yulin (Frontiers in Cellular Neuroscience, 2025)
This article conducts a systematic search of literature in the fields of neuroscience, cell biology, immunometabolism, etc. from 1990 to 2025, with PubMed/WebofScience as the core database. Experimental and clinical studies covering the core mechanisms of the preprophase of PD (mitochondrial imbalance → NLRP3 activation → lactation modification → α -SYN pathology) were included, and non-interaction mechanisms and clinical-phase studies were excluded. The pathological interaction network of mitochondrial dynamic imbalance, lysosomes - mitochondrial interaction disorder and neuroinflammation in Parkinson’s disease (PD) was explained. Construct a three-dimensional pathological network of “energy-inflammation-protein homeostasis” to provide a theoretical basis for early intervention. The imbalance of mitochondrial fission/fusion leads to the accumulation of fragmented mitochondria, triggering energy metabolism disorders and oxidative stress; abnormal aggregation of α-synuclein (α-syn) disrupts mitochondrial-endoplasmic reticulum membrane (MAM) calcium signaling, upregulates Miro protein to inhibit mitochondrial autophagy clearance, forming a vicious cycle of neuronal damage. Defects in the PINK1/Parkin pathway and LRRK2 mutations interfere with the turnover of mitochondrial fission complexes, causing mtDNA leakage, activating the NLRP3 inflammasome, and driving neuroinflammatory cascades. Additionally, lysosomal dysfunction caused by GBA1 mutations exacerbates mitochondrial quality control defects through Rab7 activity imbalance. Abnormal lactate metabolism may influence inflammasome activity through epigenetic regulation, but its role in PD needs further validation. Based on the above mechanisms, a diagnostic strategy for the prodromal phase integrating dynamic monitoring of mitochondrial fragmentation index, lysosomal function markers, and inflammatory factors is proposed, along with new intervention directions targeting Drp1, NLRP3, and the lysosome-mitochondria interface.